A conserved role for the mitochondrial citrate transporter Sea/SLC25A1 in the maintenance of chromosome integrity. - Morciano, P.; Carrisi, C.; Capobianco, L.; Mannini, L.; Burgio, G.; Cestra, G.; De Benedetto, G.E.; Corona, D.F.; Musio, A.; Cenci, G. (Human Molecular Genetics, 2009)
Histone acetylation plays essential roles in cell cycle progression, DNA repair, gene expression and silencing. Although the knowledge regarding the roles of acetylation of histone lysine residues is rapidly growing, very little is known about the biochemical pathways providing the nucleus with metabolites necessary for physiological chromatin acetylation. Here, we show that mutations in the scheggia (sea)-encoded Sea protein, the Drosophila ortholog of the human mitochondrial citrate carrier Solute carrier 25 A1 (SLC25A1), impair citrate transport from mitochondria to the cytosol. Interestingly, inhibition of sea expression results in extensive chromosome breakage in mitotic cells and induces an ATR-dependent cell cycle arrest associated with a dramatic reduction of global histone acetylation. Notably, loss of SLC25A1 in short interfering RNA (siRNA)-treated human primary fibroblasts also leads to chromosome breaks and histone acetylation defects, suggesting an evolutionary conserved role for Sea/SLC25A1 in the regulation of chromosome integrity. This study therefore provides an intriguing and unexpected link between intermediary metabolism and epigenetic control of genome stability.